2004
DOI: 10.1002/ss.113
|View full text |Cite
|
Sign up to set email alerts
|

Latinas: The new Latino majority in college

Abstract: The numbers of Latinas who attend college, stay in college, graduate, and attend graduate school escalated in the 1990s, surpassing gains made by any other underrepresented group of students in higher education. However, their achievements come at a personal cost, as the high‐achieving Latinas profiled in this chapter demonstrate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(37 citation statements)
references
References 4 publications
2
35
0
Order By: Relevance
“…Consistent with national figures, being female was found in several analyses of large scale data sets to be positively associated with academic outcomes (i.e., Arbona & Nora, 2007;Cole, 2008;Fisher, 2007;Otero, Rivas, & Rivera, 2007). Unfortunately, with the exception of work by Gonzalez, Jovel, and Stoner (2004) focused on Latinas, qualitative findings were not found to understand the differences in the experiences of male and female students and how these differences might be related to success outcomes. At the same time however, females reported receiving more gender discrimination than men from mothers, fathers, sisters, and cousins.…”
Section: Sociocultural Characteristicsmentioning
confidence: 85%
“…Consistent with national figures, being female was found in several analyses of large scale data sets to be positively associated with academic outcomes (i.e., Arbona & Nora, 2007;Cole, 2008;Fisher, 2007;Otero, Rivas, & Rivera, 2007). Unfortunately, with the exception of work by Gonzalez, Jovel, and Stoner (2004) focused on Latinas, qualitative findings were not found to understand the differences in the experiences of male and female students and how these differences might be related to success outcomes. At the same time however, females reported receiving more gender discrimination than men from mothers, fathers, sisters, and cousins.…”
Section: Sociocultural Characteristicsmentioning
confidence: 85%
“…A possible explanation is that acculturation was correlated with gender (r pb = .24, p = .01), with Mexican American female participants' acculturation scores being positively related to the decision to apply to college. Furthermore, researchers have recently reported that a growing discrepancy exists between Latina and Latino educational persistence: Latinas outnumber their male counterparts in college classrooms (González, Jovel, & Stoner, 2004;Sciarra & Whitson, 2007). A possible explanation for the increase in Latinas' educational attainment may be attributed to a desire to valerse por si misma (be self-reliant) and be able to provide for themselves rather than financially relying on a partner (Villenas & Moreno, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Historically, some Latino families believe that women should be more focused on marrying and raising families (Dayton, 2004;Gonzalez, Jovel, & Stoner, 2004). Lozano (2000) asserts this cultural belief is at odds with female students" degree attainment.…”
Section: Latinas In Higher Educationmentioning
confidence: 99%
“…Gonzalez, Jovel, and Stoner (2004) examined the challenges and sacrifices of Latina (Mexican) students who chose to leave home for the opportunity to seek a degree. The women were from low to middle socioeconomic status families and came from working class homes in California.…”
Section: Latinas In Higher Educationmentioning
confidence: 99%